THE INFLUENCE OF PRICE, PERCEIVED QUALITY, AND BRAND IMAGE ON CUSTOMER POST PURCHASE BEHAVIOUR OF FRESTEA AT PT COCA COLA AMATIL INDONESIA SEMARANG - Deka Bayu Dirgantara; Rif’ah Dwi Astuti; Erika Devie (Politeknik Negeri Semarang, 2018)
The objective of this research is to analyze the influence of price (X1), perceived quality (X2), and brand image (X3) on customers post purchase behaviour (Y) of Frestea at PT Coca-Cola Amatil Indonesia Semarang. This research used a multiple linear regression analysis. The primary data used in this research is collected from questionnaire. The amounts of the respondents are 100 who are customers of Frestea at PT Coca-Cola Amatil Indonesia Semarang. The analysis tools used were test of validity, reliability test, normality test, heteroscedasticity test, multicollinerity test, linearity test, multiple linear regression, T test, F test, the coefficient of determination and multiple linear regression. Based on the calculations using SPSS version 20, the results of this research showed that the regression equation Y = -0,007 X1 + 0,395 X2 + 0,278 X3 + e . In addition, the F test result of 18,430 which was bigger than F table was 2,70. It can be concluded the price (X1), perceived quality (X2), and brand image (X3),had a significant influence on post purchase behaviour (Y). The T test result the variable price (X1) was less than T table and had a significance bigger than level significance of 0,05. So, variables price (X1) had no influence on post purchase behaviour (Y). The variables perceived quality (X2) and brand image (X3) was bigger than T table and had a significance less than level segnificance of 0,05. So, it can be concluded the perceived quality (X2) and brand image (X3) had a positive and significance influence on post purchase behaviour (Y). The most influence variable is perceived quality (X2) with the highest regression coefficient of 0,395. The contribution of price, perceived quality, and brand image on customer post purchase behaviour is 34.6% while 65.4% are influenced by other variables that were not described in this research.